Dampak Kualitas Laporan Keuangan Desa dalam Penggunaan Aplikasi Sistem Keuangan Desa dan Sistem Pengendalian Internal - Maria Grasella Tunya; Valeria Eldyn Gula; Katharina Yuneti (Jurnal Riset Akuntansi, 2024)
This research aims to examine the impact of using village financial system applications and internal control systems on the quality of village financial reports. The research method used is quantitative with a survey approach. Data was collected using a questionnaire, and analysis was carried out using Multiple Linear Regression Analysis. The research results show that the use of village financial system applications has a positive impact on the quality of village financial reports, the internal control system also has a positive effect on the quality of village financial reports, and these two factors together have a positive and significant impact on the quality of village financial reports. Based on these findings, it is recommended that the village government in Sikka Regency improve training and ensure that village officials really understand the training material well and accurately.